Synthesis of All Four Stereoisomers of 6, 10, 13‐Trimethyltetradecan‐2‐one, a Sex Pheromone Component Produced by Males of the Stink Bug Pallantia macunaima. Issue 11 (28th February 2013) - Muraki, Yuta; Taguri, Tomonori; Yamamoto, Masanobu; Zarbin, Paulo H. G.; Ando, Tetsu
Abstract: The stink bug Pallantia macunaima (Heteroptera: Pentatomidae) is a soybean pest in southern Brazil, and the males produce 6, 10, 13‐trimethyltetradecan‐2‐one to communicate with females. All four stereoisomers of the sex pheromone were synthesized by coupling two chiral building blocks, which were synthesized from ( S )‐ and ( R )‐propylene oxides using stereospecific inversion of secondary tosylates as a key reaction. The enantiomeric purities of the building blocks were confirmed by chiral HPLC analysis. Abstract : 6, 10, 13‐Trimethyltetradecan‐2‐one is a male sex pheromone produced by Pallantia macunaima . The first synthesis of all four stereoisomers was achieved by coupling two chiral building blocks, which were made from ( S )‐ and ( R )‐propylene oxides using stereospecific inversion of secondary tosylates as a key step. The enantiomeric purities of the building blocks were confirmed by chiral HPLC analysis.